MENGENAL SOSOK MAHMUD YUNUS DAN PEMIKIRANNYA TENTANG PENDIDIKAN ISLAM - Edi Iskandar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This paper wants to elevate the figure of Mahmud Yunus and his thoughts on Islamic education. For that, at least there are some things that need to be presented, including biography and educational background, then put forward his thoughts on Islamic education. His thoughts on Islamic education are related to the goals of Islamic education, Islamic education curriculum, the institutions of Islamic education, methods of learning in Islamic education, as well as moral and ethical of educators. Mahmud Yunus's point of view about Islamic education, although the thought has existed for a long time but it still exists and is relevant in today's time, for the advancement and development of the Islamic educational institutions of the archipelago.